An investigation on cytotoxicity effect of putrescine-sulphur analogues in breast cancer (MCF-7), human lung adenocarcinoma (A549) and colorectal cancer (HCT-8) cell lines - Halim, Norsuhana; Abdul Ghani, Radiah; Sahabudin, Adzly Hairee; Fong, Fiona How Ni (2017)
Introduction: Cancer is one of the global health problems that cause detrimental to a person's life. However, the challenges in the successful chemotherapeutic nowadays are subjected to the side effects that resulted from lack of specificity in drug delivery system on cancer cells and increasing risks of systemic toxicity to the normal cells. On behalf of that, many researchers look for the alternatives in promoting the effectiveness of chemotherapeutic agent. In fact, polyamine transport system (PTS) is one of the potential pathways for transporting anticancer agent into specific cancer cells. This is due to the upregulation of PTS in cancer cells compared to normal cells for the proliferation activity. Materials and method: The cytotoxicity effects of newly synthesized putrescine-sulphur analogues type 1 (PSA-1) and type 2 (PSA-2) were evaluated in selected cancer cells; MCF-7, A549 and HCT-8 cell lines. The half-maximal inhibitory concentration (IC50) obtained from tetrazolium bromide (MTT) assay been interpolated from the dose-response graph for all cell lines. Results: PSA-2 elicited the cytotoxicity effects, eventhough the IC50 values were not potent which yielded an IC50 of (MCF-7/48h: 5.4 mM), (A549/48h: 5.2 mM) and (HCT-8/48h: 7.0 mM). In addition, the PSA-1 compound exhibited cytotoxic effect in all cell lines, however, the compounds failed to induce anti-proliferation at the concentration of 3 mM and above. The cytotoxicity of PSA-2 compound against MCF-7 cell lines showed higher potency compared to A549 and HCT-8 cell lines. Conclusion: It is suggested that PSA-2 compound able to exert the cytotoxic effects against selected cancer cells, but in low potency and is deemed to have further explore to increase the effectiveness against specific cancer cells.